A identidade cigana e o efeito de "nomeação": deslocamento das representações numa teia de discursos mitológico-científicos e práticas sociais - Fazito, Dimitri (2006)
In this article I intend to show how gypsy cultural tradition has been able to arrange a dynamic and performative identity in spite of its complex diversity. I argue that the label "gypsy", actually, is a stereotype made out of collective representations experienced by individuals of different cultural traditions along centuries of contact. The nomination effect in which social actors assymetrically positioned in the contact situation inscribe and assume collective distinctions (diacritics and frontiers) seems to strengthen the notion of "unity in diversity" present in common experiences of denial, differentiation and liminality. From a relational point of view one can observe that gypsy nomadism operates as a double face representation, a result of the coalition of mythological-scientific discourses and daily social practices: on one hand, nomadism is the terrifying consequence of endurable persecutions and exiles that are inscribed in individuals' body and reinforce the identity of common experience of difference; on the other, nomadism reinforces alterity when it is inscribed in the field of interethnic relationships as common collective experience of displacement in physical and social space.Neste artigo, procura-se mostrar como a tradição cultural cigana tem sido capaz de estabelecer uma identidade dinâmica e performativa a despeito de sua complexa diversidade. Sustenta-se que o termo "cigano" é, na realidade, um estereótipo elaborado com base em representações coletivas, experimentadas por indivíduos de diferentes tradições culturais ao longo de séculos de contato. O efeito de nomeação, pelo qual atores sociais posicionados assimetricamente na situação de contato inscrevem e assumem distinções (diacríticos e fronteiras) coletivas, parece fortalecer a noção de "unidade na diversidade", baseada nas experiências semelhantes de negação, diferenciação e liminaridade. Segundo uma perspectiva relacional, observa-se que o nomadismo cigano opera como uma representação de dupla face, resultante da fusão de discursos mitológico-científicos e práticas sociais cotidianas: de um lado, o nomadismo é o resultado aterrorizante de constantes perseguições e exílios que se inscrevem no corpo dos indivíduos e reforçam a identidade pela experiência comum da diferença; de outro, o nomadismo reforça a alteridade quando se inscreve no campo das relações interétnicas como experiência coletiva comum de deslocamento no espaço físico e social